Canva Media Development for Interactive Mathematics Learning Bar Chart Pictograms Based PBL - Damai Dwi Ramaddhina; Siti Nur Azizah; Ghaisani Shidqi Ramadhani; Alfiana Nurussama; Teten Ginanjar Rahayu (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
The purpose of this study was to examine the validity and practicality of Canva-based media through expert validation sheets and student response questionnaires. This study used 20 fourth-grade students from SDN 1 Nagrikaler as subjects, with questionnaires as the instrument used. The type of research used was R&D (Research and Development) with the ADDIE model (analysis, design, development, implementation, and evaluation). The results of the study showed that the Canva-based media “Pikgram” can be said to be very valid based on the results of the validity sheet for media experts with 97.72% and material experts with 95.16%. In addition, the Canva-based media “Pikgram” was also categorized as very practical based on the results of the student response questionnaire, which showed a score of 84.97%. This study also reinforced that the development of Canva-based digital media using the ADDIE model is feasible and can be used as a reference for the development of similar learning media.